Unrecognized introductions of SARS-CoV-2 into the US state of Georgia shaped the early epidemic. Issue 1 (15th February 2022) - Babiker, Ahmed; Martin, Michael A; Marvil, Charles; Bellman, Stephanie; Petit III, Robert A; Bradley, Heath L; Stittleburg, Victoria D; Ingersoll, Jessica; Kraft, Colleen S; Li, Yan; Zhang, Jing; Paden, Clinton R; et al.
Abstract: In early 2020, as diagnostic and surveillance responses for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ramped up, attention focused primarily on returning international travelers. Here, we build on existing studies characterizing early patterns of SARS-CoV-2 spread within the USA by analyzing detailed clinical, molecular, and viral genomic data from the state of Georgia through March 2020. We find evidence for multiple early introductions into Georgia, despite relatively sparse sampling. Most sampled sequences likely stemmed from a single or small number of introductions from Asia three weeks prior to the state's first detected infection. Our analysis of sequences from domestic travelers demonstrates widespread circulation of closely related viruses in multiple US states by the end of March 2020. Our findings indicate that the exclusive focus on identifying SARS-CoV-2 in returning international travelers early in the pandemic may have led to a failure to recognize locally circulating infections for several weeks and point toward a critical need for implementing rapid, broadly targeted surveillance efforts for future pandemics.